IOLcano Eruption: Eye on Fire With Rubeosis Iridis' Lava Flow - Joao, Alves-Ambrósio; Vítor, Miranda; Jeniffer, Jesus (Journal of Ophthalmic Science, 2023)
A 40-year-old male presented with visual impairment in the right eye (OD). He had undergone a pars plana vitrectomy for retinal detachment in the OD three years prior. Biomicroscopic examination revealed significant hyperemia, rubeosis iridis, anterior subluxation of the intraocular lens (IOL), and an organized hyphema located in the inferior third of the anterior chamber, characterized by the entrapment of iris tissue between the anterior synechia and the IOL. Figure 1. Intraocular lens anterior subluxation associated with organized hyphema and anterior iris synechia.
Keywords: Hyphema; Intraocular lens; Rubeosis iridis.